2023
DOI: 10.1007/s00234-023-03115-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between thrombus composition and stroke etiology in the MR CLEAN Registry biobank

Abstract: Purpose The composition of thrombi retrieved during endovascular thrombectomy (EVT) in acute ischemic stroke (AIS) due to large vessel occlusion (LVO) may differ depending on their origin. In this study, we investigated the association between thrombus composition and stroke etiology in a large population of patients from the Dutch MR CLEAN Registry treated with EVT in daily clinical practice. Methods The thrombi of 332 patients with AIS were histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…We observed that patients with LAA were younger (63[55-72] vs 67[59-75], P = 0.003) and had a higher rate of male (84.3% vs 44.4%, P<0.001), lower admission NIHSS (14 [9][10][11][12][13][14][15][16][17][18] vs 20 [14][15][16][17][18][19][20][21][22][23], P<0.001) and longer time from onset to puncture (300[220-440] vs 260[186-335], P<0.001) than those with CE. The prevalence of smoking history (37.9% vs 18.1%, P<0.001), hypertension (55.5% vs 40.3%, P=0.001), and tandem lesion (26.0% vs 0, P<0.001) were more in the LAA group than CE group; while the prevalence of atrial fibrillation was less in LAA group than CE group (10.7% vs 64.4%, P<0.001).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…We observed that patients with LAA were younger (63[55-72] vs 67[59-75], P = 0.003) and had a higher rate of male (84.3% vs 44.4%, P<0.001), lower admission NIHSS (14 [9][10][11][12][13][14][15][16][17][18] vs 20 [14][15][16][17][18][19][20][21][22][23], P<0.001) and longer time from onset to puncture (300[220-440] vs 260[186-335], P<0.001) than those with CE. The prevalence of smoking history (37.9% vs 18.1%, P<0.001), hypertension (55.5% vs 40.3%, P=0.001), and tandem lesion (26.0% vs 0, P<0.001) were more in the LAA group than CE group; while the prevalence of atrial fibrillation was less in LAA group than CE group (10.7% vs 64.4%, P<0.001).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Some studies have found diverse fibrin and red blood cell (RBC) proportions in clots between large-artery atherosclerosis and cardioembolic stroke. However, no significant difference has been observed between cardioembolic strokes and strokes of undetermined source [ 4 , 5 ]. Furthermore, existing data indicate that various morphologies of the left atrial appendage (LAA) exhibit diverse flow patterns and varying levels of stroke risk, with the chicken-wing type showing the lowest risk [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The thrombus composition is also related to the clinical outcomes of recanalization with thrombolysis or endovascular thrombectomy [1]. Studies have identified the pre-interventional migration, vascular origin, and age of thrombi from their histological composition and structure [2,3] , while others have differentiated cardioembolic from non-cardioembolic origin using the proportion of fibrin/platelets or red blood cells (RBCs) in thrombi [4,5].…”
Section: Introductionmentioning
confidence: 99%